Investigation of geospatial distribution of PAH compounds in soil phase and determination of soil-air exchange direction in a megacity - Yukhimets, Aigerim; Kuzu, S. Levent; Akyuz, Ezgi; Saral, Arslan (SPRINGER, 2020)
In this study, determination of possible sources, soil-air exchange direction, and spatial distribution of PAH concentrations was aimed. In this scope, soil samples were collected from 35 different points, which have the urban and rural characteristics, from European and Asian Sides in Istanbul. The average n-ary sumation (16)PAH concentrations were found as 22.11 ng/g dw for urban site and 19.53 ng/g dw for rural site, respectively. The highest concentration was 279.5 ng/g dw. PAH concentrations were higher in urban site than rural site. Acenaphthene and benzo[k]fluoranthene were observed as the dominant species. PAH concentrations are observed higher mostly in north and west parts of European Side and south and east parts of Asian Side. There was net evaporation from soil to air for lower molecular weight PAHs with 2, 3 rings, while high molecular weight PAHs with 4, 5, 6 rings accumulated in the soil at both urban and rural sites. PAHs were mostly originated from coal burning and the use of diesel engine vehicles.
Keywords: PAHs; Environmental fate; Soil-air exchange; Fugacity; Spatial distribution; POLYCYCLIC-AROMATIC-HYDROCARBONS; SEMIVOLATILE ORGANIC-COMPOUNDS; ATMOSPHERIC CONCENTRATIONS; SPATIAL-DISTRIBUTION; AGRICULTURAL SOILS; ORGANOCHLORINE PESTICIDES; POLYCHLORINATED-BIPHENYLS; SEASONAL-VARIATIONS; URBAN; PCBS; Engineering; Environmental Sciences & Ecology; Public, Environmental & Occupational Health; Water Resources